Analysis of the epidemiological profile of parturients with a diagnosis of puerperal infection in a maternity hospital in the interior of Bahia (Research, Society and Development, 2022)
The study aims to analyze the epidemiological and clinical profiles of patients diagnosed with a puerperal infection of pelvic origin in maternity in the interior of Bahia. Data collection was performed from the database of the Hospital Infection Control Comission (CCIH) and from patients' medical records included in the survey in May 2022, information on the occurrence of puerperal infection recorded between January and December 2021 was investigated. During the study period, there were 3,740 deliveries, among these, 2.46% of the patients had puerperal infection with a mean age of 28.8 years at the time of delivery. Regarding the delivery route, it was identified that cesarean section represents 94.6% of the total, and 65.2% of these women had a public prenatal follow-up. Antibiotic prophylaxis was performed in 76% of patients who subsequently had a puerperal infection.ll patients who received antibiotic therapy in this study were hospitalized. The high rate of cesarean sections contributes to the country's high rate of puerperal infection because cesarean section further exposes the patient and increases the risk of developing a puerperal infection during normal deliveries. In terms of risk factors for surgical wound infection, prolonged surgery time increases the likelihood of infection development.